(untitled) (Journal of Preventive and Social Medicine, 2025)
Background: Prescriptions are one of the prescribing standards to promote the rational use of drugs. To provide a corrective message to prescribers, it is important to evaluate prescription patterns and identify unreasonable prescribing practices. Keeping these facts in consideration the present study was planned to assess the prescription pattern using WHO prescribing indicators. Methods: The cross-sectional study was conducted at outpatient department of Dhaka Medical College Hospital and Sir Salimullah Medical College Mitford Hospital, Dhaka from January to December, 2022. A systematic random sampling technique was used to select prescriptions and data were collected by observation check list. Data were analyzed by statistical software- SPSS 23 version. Ethical issues were maintained strictly. Results: Around 296 prescriptions were analyzed. Average number of drugs per prescription was 3.5 (optimal value 1.6–1.8). About 1043 drugs were prescribed, from which 24.73% were with their generic name (optimal value 100%), antibiotics and injections were prescribed 57% (optimal value 20.0–26.8%) and 3.37% (optimal value 13.4–24.1%) respectively. About 32.7% drugs were prescribed from the Essential Drug List. During the study period, anti-ulcerant and NSAIDs were highest prescribed drug (69.3%) followed by antibiotics (57.1%). Conclusion: The study result revealed that average number of drugs per encounter, generic formatting, antibiotic prescribing, and the use of Essential Drug List (EDL) of the hospital to prescribe drugs out of the recommended values. Periodic training and initiating the performance evaluation for doctors are effective ways for improving prescription quality. There is a need to standardize the format of prescriptions so that all essential information is included. JOPSOM 2023; 42(2): 23-28